(3JCOjH GdehXajf GdOhdjjf (B/s - (3GdbGVj, eMeO HgGA YHO GdeZfjs ((3LeghQjI eUQ GdYQHjI (B:s (3OGQ GdfgVI GdYQHjI ;s (3GdEeGQGJ GdYQHjI GdeJMOI (B:s (3OGQ GdfgVI GdYdejI,s, 2017)
(3JHjf ef GdHMK Cf GdJCOjH HUaI YGeI jONd Vef GdOQGSGJ GdeJYdbI HGdLhGfH GdbGfhfjI ddhXjaI GdYGeI GdOhdjI dPG MQU GdHGMK Yd HjGf cGaI GdChLg GdbGfhfjI ShGA GdNGUI HGdCUhd GdbGfhfjI ddJCOjH GdOhdj Ch GdLQjeI GdJCOjHjI GdOhdjI Ch GdJMbjbGJ GdJCOjHjI GdOhdjI Ch GdYbhHGJ GdOhdjI Ch GdVeGfGJ GdOhdjI GdEOGQjI hfXQG dCgejI GdfXGe GdLOjO dEbGeI GdYOd GdPj Je JWHjbg HefXeI GdCee GdeJMOI, hJCKjQg Ydi GdfXGe GdJCOjHj abO Je JfGhdg HZQV GdJYQa Ydi eGgjJg(B.s
(3HHdjhLQGajI (B: (3UaMI (B323-339.s
Keywords: (3GdehXahf hGdeSDhdhf GdOhdjjfs -- (3hVY bGfhfj, bhGfjf, EdN(B.s; (3GfVHGW GdYeds -- (3bhGfjf hJTQjYGJs